The Effect Of Dividend Policy And Debt Policy On Company Value With Profitability As An Intervening Variable (Empirical Study on Construction Subsector Infrastructure Companies Listed on the IDX for the 2017-2021 Period) - Ningtias, Mitasari Wahyu; Zulkifli, Makhmud (Eco-Entrepreneur, 2023)
The purpose of this study is to determine the Effect of Dividend Policy and Debt Policy on Company Value with Profitability as an Intervening Variable (Empirical Study on Construction Subsector Infrastructure Companies Listed on the IDX for the 2017-2021 Period). The population selected by the infrastructure subsector was 29 companies, the sample was selected using the purpose sampling method of 17 companies. The variables used are dividend policy and debt policy as independent variables, company value as dependent variables, profitability as intervening variables. Research hypothesis testing using moderated regression analysis techniques with SPSS application tools. The results of this study prove that: (1) Dividend policy has a significant effect on profitability. (2) Debt policy has a significant effect on the profitability. (3) The dividend policy has no significant effect on the value of the company. (4) The debt policy has no significant effect on the value of the company. (5) Profitability has no significant effect on the value of the company. (6) The dividend policy does not affect the value of the company through profitability.  (7) The debt policy does not affect the value of the company through profitability in the construction subsector manufacturing company